The relationship between service quality and customers' satisfaction at Pejabat Pendidikan Daerah Baling Sik Kedah / Nurul Anis Abas - Abas, Nurul Anis (2014)
Nowadays, serv ice quality and c us to mers sati sfaction amon g private and public company has become a common topic. Thus, the purpose of th e study is to in vesti gate the rel ationship between servi ce quality and customers ' sati s faction at Pejabat Pendidikan Daerah Baling Sik (PPDBS) Kedah . There are three objectives developed to cover the scope of the study . The fir st objective is to identify the main fac to r of service quality that influence customers' satisfaction at PPDBS Kedah . The mean and standard deviation descriptive statistic has been used to identify the main factor of service quality that influence customers' satisfaction at PPDBS Kedah . The second objective is to investigate the relationship between service quality and customers' satisfaction at PPDBS Kedah . The Pearson Correlation Coefficient descriptive statistic has been used to identify the relationship between service quality and customers' satisfaction at PPDBS Kedah. Meantime, the third objective is to determine the significant difference in the average scores of customers' satisfaction among male and female respondents. The independent t-test descriptive statistic has been used to analyze the differences between male and female respondents. Otherwise, there are 150 questionnaires distributed among PPDBS Kedah customers. The total of the questionnaires can be used to analyze the data and used to determine all the objectives are 107 questionnaires. Therefore, the total of the respondents are I 07 respondents. Others, the finding of the study shows the highest relationship between service quality and customers' satisfaction is human element of service delivery. A s for recommendation, this study helps PPDBS Kedah improve service quality and can increase the level of customers' satisfaction toward the service provided to customers.